Colombia : Staff Report for the First Review Under the Extended Arrangement. (IMF Staff Country Reports; Country Report, 2001)
Colombia's economic performance deteriorated markedly in the last half of 1998 and during 1999 under the combined influence of external shocks and a weakening of confidence. In an effort to reverse the deterioration, the authorities developed a multiyear stabilization and reform program based on fiscal consolidation, exchange rate flexibility bank restructuring, and structural reforms. Indications suggested that economic activity in Colombia has been recovering and the IMF-supported extended program remains on track. The IMF staff welcomed the authorities' reaffirmation of the strategies and policies underlying the program.